Learning networks in innovation systems at sector / regional level in Argentina: Winery and dairy industries - Sanchez, Guillermo; Bisang, Roberto Oscar (2017)
This work studies how the set of relationships that gives place to the learning processes is established in the food industry in Argentina. A theoretical ad hoc approach is adopted, conjugating the concepts of innovation systems at sector / regional level with some context considerations like the innovative behaviour of the global and local food industry and a description of the public and private S&T in Argentina. The study is focused in two cases: the wine industry, at the Mendoza province, and the dairy products industry at the centre of the Santa Fe province, both in Argentina. While the winery industry at the province of Mendoza exports differentiated products the dairy industry, at the central basin of the province of Santa Fe, exports commodities leaving differentiated (functional) products for the domestic market. These facts determine different dynamics between them, despite of what the established set of relationships is very complex and knowledge intensive in both cases. Also, in both cases the preponderant contribution of the public institutions of science and technology as knowledge and technology source is flagged